The Mediating Role of the Participatory Leadership Style on the Effect of Job Stress on Job Performance - Abd, Ibraheem Mohammed; Zuhairi, Mustafa Mohammed Kleban; Kamil, Ghaith Hasan (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
The aim of the current study is to shed light on the impact of workplace stress on job performance in Iraqi public sector universities through the mediating role of leadership style. Where stresses in the workplace were measured through three types: role conflict, role burden and work conditions, job performance was determined as a dependent variable, the participatory leadership style was tested as a mediating variable for the relationship, the structural equation modeling method was applied to test the study model. A sample of professors of public universities in Iraq-Baghdad was selected, and 120 answers were collected that were valid for analysis. The study concluded that conflicting roles and working conditions are the factors that have an impact on academic performance. In contrast to the workload, which did not have a statistically significant effect on the performance of university professors. As for the mediation role of participatory management, it was contrary to expectations. It was not a contributing factor in reducing the effects of work stresses on the performance of university professors. These results are attributed to the fact that the university work environment affects its leaders and professors and is governed by the instructions and regulations of higher authorities.